2020
DOI: 10.1111/dth.13627
|View full text |Cite
|
Sign up to set email alerts
|

Hidden threat lurking behind the alcohol sanitizers in COVID ‐19 outbreak

Abstract: The ongoing COVID‐19 pandemic has made various challenges for communications all over the world. Nowadays hand hygiene practices with alcohol sanitizers are an unavoidable reality for many people, which cause skin dryness and flaking. The current short communication has been explained about monitoring the quality control of alcohol concentrations and hand rub formulation, which needs more attention and should consider meticulous in this crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…Those who use alcohol-based hand washing products have increased skin problems. 1,20,23 Contact dermatitis is an inflammatory response. 24 Irritant contact dermatitis is the most common form of occupational dermatoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who use alcohol-based hand washing products have increased skin problems. 1,20,23 Contact dermatitis is an inflammatory response. 24 Irritant contact dermatitis is the most common form of occupational dermatoses.…”
Section: Discussionmentioning
confidence: 99%
“…Although hand washing with soap is the most recommended method, products containing ethanol are used in cases where water cannot be reached. Those who use alcohol‐based hand washing products have increased skin problems 1,20,23 . Contact dermatitis is an inflammatory response 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this not only led to panic buying and overuse of sanitizers but also increased the supply of substandard products in the markets [ 14 ]. These products have limited antiviral activity, leading to the emergence and re-emergence of some microorganisms and dermatological problems [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…6). Emami reported that frequent use of alcohol based products can result in skin dryness and irritation [26]. Rundle reported that 98% of cases had irritant contact dermatitis due to frequent hand washing [9].…”
Section: % Hcws Who Answered the Question About The Types Of Face Masmentioning
confidence: 99%